Miri City Council / Eileen Richad - Richad, Eileen (University Technology MARA Sarawak, 2019)
The establishment of the Council may be traced back to the early 1930s. 1933, the Miri Municipal Board was established following the enactment of the Municipal Order No. M-7, 1933. The Board consisted of the Resident, 4th Division as Chairman, together with the Municipal Officer and a few community leaders as members. It continued to function up to December, 1941 when it was interrupted by Japanese Occupation until 1945. On 1st January, 1956 the Miri Municipal Board was re-constituted and became the Miri Urban District Council, financially self-supporting and managing its own local affairs. The Council consisted of 17 members, all of whom were nominated. In December, 1960 a Council's general election was held for the first time in Miri. The fully elected Council constituted under the Local Authority (Miri District Council) Order 1960, began functioning on 9th January, 1961. Under the new constitution, the Council was changed from the Urban District Council to the status of a District Council in order to meet the requirements of new development in the field of local government, and with the object of extending its boundaries to include the whole of the Miri administrative sub-district. The Council consisted of 18 elected members. The Divisional Engineer, the Superintendent of Lands and Surveys, the Divisional Medical Officer, the Divisional Education Officer and the Superintendent of Police were advisers to the Council.